2021
DOI: 10.1038/s41419-021-04187-5
|View full text |Cite
|
Sign up to set email alerts
|

Chidamide triggers BTG1-mediated autophagy and reverses the chemotherapy resistance in the relapsed/refractory B-cell lymphoma

Abstract: Rituximab/chemotherapy relapsed and refractory B cell lymphoma patients have a poor overall prognosis, and it is urgent to develop novel drugs for improving the therapy outcomes. Here, we examined the therapeutic effects of chidamide, a new histone deacetylase (HDAC) inhibitor, on the cell and mouse models of rituximab/chemotherapy resistant B-cell lymphoma. In Raji-4RH/RL-4RH cells, the rituximab/chemotherapy resistant B-cell lymphoma cell lines (RRCL), chidamide treatment induced growth inhibition and G0/G1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…As for the protective prognostic factors in our study, PXK encoding protein is involved in ligand-induced internalization, synaptic transmits, and degradation of epidermal growth factor receptors associated with some autoimmunity diseases ( Takeuchi et al, 2010 ). B-cell translocation gene 1 (BTG1) belongs to an anti-proliferative gene family, which regulates autophagy and the cell cycle and is also implicated in DNA repair and mRNA stability ( Xue et al, 2021 ). BTG1 is a well-characterized tumor suppressor for both solid tumors and hematopoiesis and recently has been reported to have a novel role in genotoxic and integrated stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…As for the protective prognostic factors in our study, PXK encoding protein is involved in ligand-induced internalization, synaptic transmits, and degradation of epidermal growth factor receptors associated with some autoimmunity diseases ( Takeuchi et al, 2010 ). B-cell translocation gene 1 (BTG1) belongs to an anti-proliferative gene family, which regulates autophagy and the cell cycle and is also implicated in DNA repair and mRNA stability ( Xue et al, 2021 ). BTG1 is a well-characterized tumor suppressor for both solid tumors and hematopoiesis and recently has been reported to have a novel role in genotoxic and integrated stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…218 There are several studies using the ChIP technique to confirm whether alterations in chromatin structure and expression of certain genes are restored after epidrug treatment. [219][220][221] MS has been used to determine the altered structure of proteins of interest, although there are limitations in recognizing the large number of ions inherent to histones or other cellular proteins. Different algorithms have been developed depending on the integrity of the quantified protein (total, peptides or amino acids), THRASH journals.sagepub.com/home/tah TherapeuTic advances in hematology being one of the most versioned although it still depends on the structural reference database.…”
Section: Computational Validation Of Epigenetic Alterations In B-and ...mentioning
confidence: 99%
“…rituximab/chemotherapy resistant B-cell lymphoma (RRCL) patients are characterized with poor prognosis, while tucidinostat reverses the chemotherapeutic resistance through B-cell translocation gene 1 (BTG1)-mediated autophagy. Tucidinostat shows synergistic effect with chemotherapeutics, such as etoposide, cisplatin, gemcitabine, in RRCL cell lines (Xue et al, 2021). Zhang et al showed that tucidinostat and doxorubicin exhibited a synergistic effect in 2 PTCL cell lines through increased DNA damage and apoptosis (Zhang et al, 2017).…”
Section: Hematological Malignanciesmentioning
confidence: 99%